The association between calcium consumption and students body composition - Zając, Przemysław; Grochowska, Aneta; Suliga, Edyta (Medical Studies/Studia Medyczne, 2017)
Introduction: The consumption of calcium in the Polish population is insufficient, which may negatively influence the occurrence of osteoporosis, as well as cause overweight and obesity. Aim of the research : To analyse the relationship between calcium consumption and body composition of the participants of this study. Material and methods : The study was carried out on a sample group of 103 nursing students. The study group consisted of 91 (88.3%) women and 12 (11.7%) men, aged from 19 to 33 years. The participants of the study had their body composition analysed, the body mass index (BMI) was calculated, and the authors carried out a survey involving the Dairy Products Frequency Questionnaire (ADOS-Ca) as well as their own questionnaire to evaluate the socio-economic status of the subjects. Results : The students who had the lowest calcium consumption also had the lowest BMI (p = 0.0015) and the lowest amount of visceral fat (p = 0.0260). Individuals who consumed the lowest amount of calcium also had the lowest muscle mass (p = 0.007) and bone mass (p = 0.004). However, the authors did not notice a significant statistical difference between the level of calcium consumption and the percentage of adipose tissue (p = 0.5000) as well as body water percentage (p = 0.3200). Conclusions: The results of the research do not confirm the hypothesis that high calcium consumption is associated with a lower probability of the occurrence of excess body mass and adipose tissue.